Clinical and quality of life outcomes following reduction mammoplasty for symptomatic macromastia among Sri Lankan women: A prospective observational study - Kanchana Wijesinghe; Umesh Jayarajah; Malllawaarchchige Gayan Ranjan Mallawaarachchi; Sumali Hirunika De Silva; Thathya Thamarasie Wardana De Silva; Ananthmoorthy Krishnamoorthy; Dissanayaka Mudiyanselage Shihanie Rubeka; Ajith De Silva (Asian Journal of Medical Sciences, 2023)
Background: The impact of macromastia is unfortunately underestimated among developing South Asian countries. However, it remains a common cause of physical and emotional suffering among women. Aims and Objectives: We aimed to evaluate the efficacy of reduction mammoplasty in alleviating symptoms of macromastia and its impact on quality of life (QOL) among Sri Lanka females. Materials and Methods: A prospective study was conducted among 48 patients who underwent reduction mammoplasty in a surgical unit in Sri Lanka. SF-36 questionnaire and a Visual Analog Scale were used to assess QOL and pain. The outcomes were assessed 1 week prior and at 2 weeks and 6 months after surgery. Results: Median age was 43 years and the median body mass index was 26.8 kg/m2. The average duration of symptoms was 2 years. All patients initially were reluctant to seek medical advice. Only 10.4% of patients were aware of the availability of treatment. Wise-pattern reduction mammoplasty was performed in 79.2%. There was a significant reduction in pain following surgery. There was also an improvement in all domains of the QOL following surgery, especially in general health, pain, and physical functions. Conclusion: Reduction of mammoplasty caused a significant improvement in the overall QOL with the reduction in pain for patients suffering from macromastia. Creating more awareness among the public to encourage women to discuss breast-related symptoms and to overcome sociocultural taboos is a timely necessity.